African-specific polymorphisms in Plasmodium falciparum serine repeat antigen 5 in Uganda and Burkina Faso clinical samples do not interfere with antibody response to BK-SE36 vaccination - Arisue, Nobuko; Palacpac, Nirianne Marie Q.; Ntege, Edward H.; Yeka, Adoke; Balikagala, Betty; Kanoi, Bernard N.; Bougouma, Edith Christiane; Tiono, Alfred B.; Nebie, Issa; Diarra, Amidou; Houard, Sophie; D’Alessio, Flavia; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
BK-SE36, based on Plasmodium falciparum serine repeat antigen 5 (SERA5), is a blood-stage malaria vaccine candidate currently being evaluated in clinical trials. Phase 1 trials in Uganda and Burkina Faso have demonstrated promising safety and immunogenicity profiles. However, the genetic diversity of sera5 in Africa and the role of allele/variant-specific immunity remain a major concern. Here, sequence analyses were done on 226 strains collected from the two clinical trial/follow-up studies and 88 strains from two cross-sectional studies in Africa. Compared to other highly polymorphic vaccine candidate antigens, polymorphisms in sera5 were largely confined to the repeat regions of the gene. Results also confirmed a SERA5 consensus sequence with African-specific polymorphisms. Mismatches with the vaccine-type SE36 (BK-SE36) in the octamer repeat, serine repeat, and flanking regions, and single-nucleotide polymorphisms in non-repeat regions could compromise vaccine response and efficacy. However, the haplotype diversity of SERA5 was similar between vaccinated and control participants. There was no marked bias or difference in the patterns of distribution of the SE36 haplotype and no statistically significant genetic differentiation among parasites infecting BK-SE36 vaccinees and controls. Results indicate that BK-SE36 does not elicit an allele-specific immune response.